Correlation of Cervical Vertebral Maturation and Tooth Mineralization of Mandibular Second Molar - Muhammad Kamran; Gulsana Hashmi; Muhammad Noman; Umar Hussain (Gandhara University, 2023)
OBJECTIVES To determine the correlation between skeletal maturity and mandibular second molar calcification. METHODOLOGY A descriptive cross-sectional study was conducted at the Saidu College of Dentistry from 15th January to 30th October 2022. One hundred participants of Pakistani descent, aged 8-16 years (both genders), with ANB greater than 50 and presence of all permanent teeth excluding 3rd  molars, were included. Medically compromised, syndromic patients, those who had undergone previous orthodontic treatment, and cases with extracted permanent teeth were excluded. Skeletal maturity was determined by analyzing the cervical vertebrae maturation index (CVMI) on lateral cephalogram according to Baccetti et al. and mandibular second molar calcification according to the Demijian Index from panoramic radiographs. The Spearman correlation test was run for correlation assessment. RESULTS The mean age was 11.81±1.62 years. There were 49 (49%) males and 51 (51%) females. A perfect correlation (100%) was found between CVM stage I and dental stage C. The concordance between CVM stage II and dental stage D was found in 21 (91.30%). The correlation between tooth mineralization and CVM stages was very high and statistically significant (r=0.97, p<0.001). Similarly, the correlation between CVM and chronological age was also high and statistically significant (r=0.8, p<0.001). The correlation was also significantly increased in males and females (r=0.97, p<0.001). CONCLUSION The tooth mineralization stages of the mandibular second molar can be used to assess growth as an alternative to cervical maturation staging.